Dunc's doll - Paulsen, Gary. (New York, N.Y. : Dell, 1992)
Dunc Culpepper and his friend Amos pursue a band of doll thieves in possession of a valuable antique doll.
"A Yearling book."
Accelerated Reader AR
Keywords: Dolls -- Juvenile fiction; Mystery fiction